Manejo integrado de Afido Amarillo (Sipha flava), en el cultivo de Caña de Azúcar (Saccharum officinarum) - Zapata Loor, Edwin Abdala (2025)
The yellow aphid (Sipha flava) is a highly significant pest that affects sugarcane crops, resulting in substantial losses in advanced cycles. This study aims to describe the Integrated Management of the Yellow Aphid (Sipha flava) in Sugarcane Crops and evaluate the effectiveness of integrated management in controlling the yellow aphid population in sugarcane crops. Since integrated management consists of a combination of biological control techniques, such as introducing natural predators, chemical products, using selective insecticides, and cultural methods, such as changes in agricultural practices. The results showed that integrated management significantly reduced yellow aphid populations and improved sugarcane production. It was also observed that the use of chemical pesticides decreased, and biodiversity in agro-ecosystems increased. This study demonstrates that integrated management is an effective strategy for controlling the yellow aphid population and improving sugarcane production sustainably. In conclusion, we have that integrated pest management is essential, as it will help prevent sugarcane crops from being affected in an uncontrolled manner, resulting in severe losses. This control method can limit yellow aphid infestations, which may vary depending on the age of the sugarcane plants. It is common for sugarcane crops to be more susceptible to the yellow aphid during the dry season.